2020
DOI: 10.1186/s12883-020-01963-2
|View full text |Cite
|
Sign up to set email alerts
|

Comaneci device-assisted embolization of wide-necked carotid aneurysms with an unfavorable ratio

Abstract: Background Endovascular treatment is the technique of choice for most intracranial aneurysms. However, the treatment of morphologically complex wide-necked aneurysms with an unfavorable anatomy is still a therapeutic challenge. The purpose of the study is to describe the initial experience with the Comaneci embolization assist device for the treatment of wide-necked aneurysms with an unfavorable ratio for direct embolization. Methods We report a retrospective single-center analysis taken from a prospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…[4,5,7] Variations of the technique including stent-assisted coiling and balloonassisted coiling were developed in attempts to overcome some of these barriers and have been shown to be effective in management of aneurysms with an unfavorable ratio. [5,10] However, these techniques are not without limitations. BAC halts forward blood flow compromising end-organ perfusion and can also cause vessel damage increasing risk of thromboembolic events or aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4,5,7] Variations of the technique including stent-assisted coiling and balloonassisted coiling were developed in attempts to overcome some of these barriers and have been shown to be effective in management of aneurysms with an unfavorable ratio. [5,10] However, these techniques are not without limitations. BAC halts forward blood flow compromising end-organ perfusion and can also cause vessel damage increasing risk of thromboembolic events or aneurysm rupture.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 , 7 ] Variations of the technique including stent-assisted coiling and balloon-assisted coiling were developed in attempts to overcome some of these barriers and have been shown to be effective in management of aneurysms with an unfavorable ratio. [ 5 , 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Comaneci device (Rapid Medical, Yokneam, Israel), introduced to the US in 2019, is a retrievable stent that can be used along with coiling for better occlusion of wide-necked aneurysms without limiting blood flow [ 76 ]. Molina-Nuevo et al concluded that the Comaneci device is a safe adjunctive treatment option for wide-necked aneurysms, with a complete occlusion rate of 88.8% and a major complication rate of 5.6% among 16 patients [ 77 ].…”
Section: Reviewmentioning
confidence: 99%